Peran Pendidik Dalam Mengembangkan Kreativitas Seni Anak Usia Dini Di Kelompok Bermain Koronka Bawen Kabupaten Semarang - Wahyu Trisnawati; Tri Joko Raharjo; Bagus Kisworo (Jendela PLS: Jurnal Cendekiawan Ilmiah Pendidikan Luar Sekolah, 2021)
Developing creativity in the classroom is a major factor that matters. Educators who understand creativity can help learners in developing creativity. Educators who train and teach creativity must be educators who have a creative soul. The outline of the issue examined was how the role of educators in developing early childhood art creativity in Group Play Koronka, how to factor endowments development early childhood art creativity in Group Play Koronka, as well as how the factors restricting the development of creativity in early childhood Arts Groups Play Koronka. data collection is carried out by means of observation, interview and documentation. The validity of the data obtained through triangulation of sources and methods. Data analysis starts from data collection through the reduction of the data, the presentation of data, and the withdrawal of the conclusion. The results obtained in this research is the role of educators include educating, teaching, guiding, directing, train, assess, and evaluate his protégé participant about the creativity of art. Educators who creatively very influential towards the participants of his protégé. In addition, the factors that support the creativity of art comes from the support of parents as well as adequate infrastructure and facilities. While the factors that inhibit the creativity of art located on educators or parents who break the idea put forth child, competition between the child, the limitation on the child's curiosity, many educators forbid children, as well as parenting parents too keep an eye on the child.